2017
DOI: 10.1038/bjc.2017.118
|View full text |Cite
|
Sign up to set email alerts
|

One-carbon metabolism in cancer

Abstract: Cells require one-carbon units for nucleotide synthesis, methylation and reductive metabolism, and these pathways support the high proliferative rate of cancer cells. As such, anti-folates, drugs that target one-carbon metabolism, have long been used in the treatment of cancer. Amino acids, such as serine are a major one-carbon source, and cancer cells are particularly susceptible to deprivation of one-carbon units by serine restriction or inhibition of de novo serine synthesis. Recent work has also begun to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
328
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(334 citation statements)
references
References 54 publications
6
328
0
Order By: Relevance
“…Cancer cells require high quantities of energy and anabolic resources to support their rapid cell division; therefore, their key metabolic pathways are altered. 34,35 Notably, we observed that elevated levels of the purine catabolic pathway metabolites hypoxanthine and uric acid were associated with AAs with BLCA. 32,33 Overall, our platform was able to identify altered metabolites and associated pathways in AA BLCA versus EA BLCA.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Cancer cells require high quantities of energy and anabolic resources to support their rapid cell division; therefore, their key metabolic pathways are altered. 34,35 Notably, we observed that elevated levels of the purine catabolic pathway metabolites hypoxanthine and uric acid were associated with AAs with BLCA. 32,33 Overall, our platform was able to identify altered metabolites and associated pathways in AA BLCA versus EA BLCA.…”
Section: Discussionmentioning
confidence: 76%
“…This metabolic pathway supports several physiological processes that provide one-carbon units for methylation reactions, nucleotide synthesis, amino acid homeostasis, and reductive metabolism, which support the high proliferation of cancer cells. 34,35 Notably, we observed that elevated levels of the purine catabolic pathway metabolites hypoxanthine and uric acid were associated with AAs with BLCA. Recent studies have demonstrated that elevated levels of uric acid in serum are associated with greater cancer risk, recurrence, and mortality in colorectal, breast, and prostate cancers, [36][37][38] and its proinflammatory properties may play a role in BLCA pathogenesis in AAs.…”
Section: Discussionmentioning
confidence: 76%
“…Some previous studies have associated carbon metabolism with carcinogenesis, mainly due to its role in DNA synthesis (Newman and Maddocks, ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another pathway of intense interest in cancer in recent years is one‐carbon metabolism, mainly due to the need of cancer cells to support enhanced proliferation and survival (Ducker and Rabinowitz, ; Newman and Maddocks, ). In this study, multiple pathway metabolites were significantly altered (glycine, sarcosine, SAH, methionine, homocysteine; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that this defect in cancerous, as compared to normal, cells could be used for therapeutic purpose 911 . A methionine-free diet or methionine-deprived total parenteral nutrition causes regression of a variety of animal tumors 12 . It has also been suggested that vegan diets, containing relatively lower methionine, may be a useful nutritional strategy controlling for cancer growth 13 .…”
Section: Introductionmentioning
confidence: 99%